Wave-packet continuum-discretization approach to ion-atom collisions: Non-rearrangement scattering - Abdurakhmanov, I.; Kadyrov, Alisher; Bray, I. (American Physical Society, 2016)
A general single-center close-coupling approach based on a continuum-discretization procedure is developed to calculate excitation and ionization processes in ion-atom collisions. The continuous spectrum of the target is discretized using stationary wave packets constructed from the Coulomb wave functions, the eigenstates of the target Hamiltonian. Such continuum discretization allows one to generate pseudostates with arbitrary energies and distribution. These features are ideal for detailed differential ionization studies. The approach starts from the semiclassical three-body Schrödinger equation for the scattering wave function and leads to a set of coupled differential equations for the transition probability amplitudes. To demonstrate its utility the method is applied to calculate collisions of antiprotons with atomic hydrogen. A comprehensive set of benchmark results from integrated to fully differential cross sections for antiproton-impact ionization of hydrogen in the energy range from 1 keV to 1 MeV is provided. Contrary to previous predictions, we find that at low incident energies the singly differential cross section has a maximum away from the zero emission energy. This feature could not be seen without a fine discretization of the low-energy part of the continuum.